Heat Adaptation in Military Personnel: Mitigating Risk, Maximizing Performance - Parsons, Iain T.; Stacey, Michael J.; Woods, David R. (Frontiers in Physiology, 2019)
The study of heat adaptation in military personnel offers generalizable insights into a variety of sporting, recreational and occupational populations. Conversely, certain characteristics of military employment have few parallels in civilian life, such as the imperative to achieve mission objectives during deployed operations, the opportunity to undergo training and selection for elite units or the requirement to fulfil essential duties under prolonged thermal stress. In such settings, achieving peak individual performance can be critical to organizational success. Short-notice deployment to a hot operational or training environment, exposure to high intensity exercise and undertaking ceremonial duties during extreme weather may challenge the ability to protect personnel from excessive thermal strain, especially where heat adaptation is incomplete. Graded and progressive acclimatization can reduce morbidity substantially and impact on mortality rates, yet individual variation in adaptation has the potential to undermine empirical approaches. Incapacity under heat stress can present the military with medical, occupational and logistic challenges requiring dynamic risk stratification during initial and subsequent heat stress. Using data from large studies of military personnel observing traditional and more contemporary acclimatization practices, this review article (1) characterizes the physical challenges that military training and deployed operations present (2) considers how heat adaptation has been used to augment military performance under thermal stress and (3) identifies potential solutions to optimize the risk-performance paradigm, including those with broader relevance to other populations exposed to heat stress.